WORK ON POTENTIAL LEXICAL MATERIAL IN TEACHING READING TEXTS BY SPECIALTY OF ADULT STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
The article suggests methods of teaching potential vocabulary as one of the ways of enlarging the lexical stock of adult learners, the peculiarities of development of their memory and cognitive processes being taken into consideration.